A new species of Haliclona (Demospongiae: Haplosclerida: Chalinidae) from southeastern Brazil and the first record of Haliclona vansoesti from the Brazilian coast - Muricy, Guilherme; Esteves, Eduardo L.; Monteiro, Leandro C.; Rodrigues, Beatriz Roma; Albano, Rodolpho M. (Zootaxa, 2015)
In this paper we describe two species of the cosmopolitan sponge genus Haliclona from Rio de Janeiro State, SE Brazil, one of which is new to science and the other a new record to Brazil. Haliclona (Rhizoniera) fugidia sp. nov. is brownish-pink, salmon or cream, thickly encrusting, without oscular tubes and tangential ectosomal reticulation. Choanosomal skeleton is a mostly unispicular ladder-like reticulation of oxeas, very organized near the sponge surface and denser and more disorganized in the interior of the sponge. Haliclona (Halichoclona) vansoesti de Weerdt et al., 1999 was originally described from the Caribbean. It has a very loose connection between ectosome and choanosome, a whitish translucent ectosome combined with a purplish choanosome, a cavernous structure and a friable or crispy consistency. The conspecificity of SE Brazilian and Caribbean populations of H. (Halich.) vansoesti was verified through phylogenetic analysis of small subunit 18S rRNA (18S) and mitochondrial cytochrome oxidase subunit I (COI) gene sequences. A maximum likelihood phylogenetic tree constructed with 18S sequences indicates that specimens of H. (Halich.) vansoesti from Rio de Janeiro were phylogenetically closer to the same species from the Caribbean than to other species of Haliclona. Although not available for H. (Halich.) vansoesti from the Caribbean, COI sequences of our specimens were also quite distinct from those of other Haliclona species. Molecular identification based on DNA sequences is a useful complement to traditional morphology-based taxonomy, especially in highly plastic sponges such as Haliclona spp. and other haplosclerids.